DETERMINAÇÃO E ESTUDOS DE ESTRUTURAS DE COMPLEXOS ENZIMALIGANTES RELEVANTES À BIOLOGIA DAS PTERIDINAS EM PARASITAS: BASE PARA O DESENVOLVIMENTO RACIONAL DE DROGAS TERAPÊUTICAS CONTRA DOENÇA DO SONO - Martini, Viviane Paula (2007)
The enzymes dihydrofolate reductase-thymidylate synthase (DHFR-TS) and pteridine reductase (PTR) are involved in the pterin/folate dependent metabolism; together they represent an important target for chemotherapy of parasitic leishmanias and trypanosomes. Xray crystallography was used to elucidate accurately the structure of the PTR1 enzyme from Trypanosoma brucei in complex with inhibitors which are analogous to the substrate. The ligands assayed for crystallization were the substrate folate and the inhibitors melamine, 6-thioguanine, WSG1012, WSG1034, WSG3065, WSG3066 and WSG3067. Of these, four yielded crystals with diffraction patterns sufficient for a complete dataset. WSG3065 (later revealing the lack of the ligand), WSG3066 and WSG3067 are three of the several structures presented in this work which came from the cited crystallization assays; added to these are the refined structures complexed with triamterene and cyromazine, proceeded from two other datasets already available. The datasets were processed with the programs Mosflm / Scala and Xds / Xscale, the structures were refined using the programs CNS and Refmac5 and validated with the programs Procheck, Whatcheck, Sfcheck and ValidationPDB. All refined structures belong to the space group P21 with unit cells around a = 79, b = 90, c = 82, b = 115, 4 monomers each of 268 residues per asymmetric unit and complex active sites. Besides the inhibiting ligands (except WSG3065) present in the structure, other ligands were found either near or outside the active site: dithiothreitol, glycerol, ethylene glycol, sodium and acetate ions. Analyses on the ligand positions and corresponding interactions with the protein were carried out to understand modes of inhibition and to guide the design or the discovery of new compounds which are potent, but selective to the parasitic enzyme, inhibitors. Thereby, initial docking studies were performed aiming at identifying new molecules or lead compounds with inhibitory capabilities.